HUMAN RESOURCES READINESS IN WELLNESS TOURISM MANAGEMENT IN THE SENIOR TOURIST MARKET SHARE IN INDONESIA - Violetta Simatupang; Sukmadi Sukmadi; Wisnu Bawa Tarunajaya; ER Ummi Kalsum (International Journal of Social Science, 2022)
Wellness tourism has now become a trend in the world community, especially after the Covid 19 pandemic. The main goal of wellness tourism is to achieve fitness and health and gain self-satisfaction. Wellness tourism has the potential to be developed in Indonesia, especially for the senior tourist segment. This research was conducted with a qualitative descriptive approach using primary and secondary data. Based on the research results, it can be seen that (1) the readiness of tourism Human Resources (HR) in managing the wellness tourism in the market share of senior tourists is currently not fully ready and the number is fulfilled. Based on survey results at 2 wellnes tourism, the HR used is not HR in the tourism sector. The role of education in improving HR capabilities in the development of wellness tourism as well as knowledge related to senior market share is urgently needed. Services and needs for senior tourists are different from tourists in general. Tourism education is one of the keys in developing tourism potential, especially in the field of wellness tourism business.; (2) Development of Wellness Tourism in Indonesia continues to be encouraged by the Minister of Tourism and Creative Economy, to revive the tourism sector and the creative economy in the country; socialization is needed to stakeholders and the general public regarding this matter in order to get the necessary understanding and support (3) The government needs to make references regarding the definition of senior tourists, from the aspects of their age, physical ability, character and special needs in managing the wellness business.